Effective playing time affects physical match performance in soccer: An analysis according to playing position - Altmann, Stefan; Forcher, Leon; Woll, Alexander; Härtel, Sascha (Biology of Sport, 2023)
This study aimed to analyse the influence of effective playing time on physical match performance according to playing position in professional soccer. Official match data from 267 matches (3,731 single observations) during the 2018/2019 season of the German Bundesliga were used and the effective playing time (duration of play after subtracting the time taken up by stoppages, substitutions, injuries, and goals) was captured for each match. The physical match performance parameters total distance, high-intensity distance, sprinting distance, maximum velocity, and accelerations were analysed. Players were categorized as central defender, wide defender, central defensive midfielder, central offensive midfielder, wide midfielder, and forward. Effective playing time influenced physical match performance, with total distance and accelerations (r = 0.48–0.61) being the most and high-intensity distance, sprinting distance, and maximum velocity (r = -0.17–0.03) the least affected parameters. Players covered on average 10% more total distance and performed 13% more accelerations, while sprinting 7–10% less in matches with long (> 65 min) compared to short (< 50 min) effective playing times. The influence of effective playing time was rather similar between playing positions. Still, physical performance of wide midfielders and forwards partly deviated from the pattern observed in the other positions. Coaches and practitioners should be aware that effective playing time influences physical match performance in the German Bundesliga, while special attention should be given to wide midfielders and forwards. Effective playing time and its general and position-specific effects should be taken into account when interpreting physical match performance, thereby facilitating load management practices and training design.